Employee Engagement as An Effort to Improve Work Performance: Literature Review - Dian Bagus Mitreka Satata (Ilomata International Journal of Social Science, 2021)
Employee engagement is a physical and psychological condition related to work cognitively, emotionally, and behavior to achieve the goals of the organization. The purpose of writing this review article is to summarize and discuss employee engagement as an effort factor in improving work performance within the organization. The method used is a literature review, which is a literature review search for both international journals and national journals between 2013 – 2020 as many as 15 journal articles from the results of previous research. The results of the literature review show that employee engagement has an influence on individual work performance so that organizational goals can be achieved.